The Influence of Service Quality and Price on Customer Loyalty at PT. Tri Sapta Jaya Sibolga - Anjela, Rina (Journal of Economics, Management and Accounting (JEMA), 2025)
This study aims to examine the influence of Service Quality and Price on Customer Loyalty at PT. Tri Sapta Jaya Sibolga. The research sample consisted of 41 customers in May 2025 at PT. Tri Sapta Jaya Sibolga. The research method used was quantitative with a descriptive approach. Data collection was conducted using a questionnaire with a Likert scale, while the data analysis employed Classical Assumption Tests and other statistical tests. The results of the study indicate a perfect correlation of the variables Service Quality (X1) and Price (X2) simultaneously on Customer Loyalty (Y) at PT. Tri Sapta Jaya Sibolga, with a significance value of F-change = 0.000 < 0.05 and an R value of 0.856. The effect of Service Quality (X1) on Customer Loyalty (Y) was shown by t-count > t-table, namely 3.860 > 2.028. This means that the initial hypothesis (Ha) is accepted, and it can be concluded that Service Quality (X1) partially has a positive and significant effect on Customer Loyalty (Y). The effect of Price (X2) on Customer Loyalty (Y) was shown by t-count > t-table, namely 7.056 > 2.028, indicating that the initial hypothesis (Ha) is accepted, and it can be concluded that Price (X2) partially has a positive and significant effect on Customer Loyalty (Y). The regression equation obtained is: Y = 2.697 + 0.354X1 + 0.584X2. From the F-test, the value of F-count > F-table, namely 52.111 > 3.24, so H0 is rejected. This indicates that there is a positive simultaneous effect of Service Quality (X1) and Price (X2) on Customer Loyalty (Y) at PT. Tri Sapta Jaya Sibolga. The coefficient of determination (R²) is 0.733, which practically means that Service Quality (X1) and Price (X2) together contribute 73.3% to Customer Loyalty (Y), while the remaining 26.7% is influenced by other variables not examined in this study.